Pre-exposure prophylaxis implementation during incarceration: Perspectives of formerly incarcerated men and women. - Elizabeth Anna Banyas; Madelaine F Castleman; Husnah A Rahim; Eunice Okumu; Becky L White (PLoS ONE)
The HIV prevalence is higher among individuals involved in the United States (U.S.) correctional system than those in general population. Despite this, people in prisons or other closed settings have poor access to the most effective biomedical prevention tool, HIV pre-exposure prophylaxis (PrEP). The purpose of this study was to explore the attitudes and beliefs of PrEP initiation in correctional facilities amongst individuals formerly in prisons or other closed settings. We conducted 13 in-depth qualitative interviews with recently released (from incarceration) clients participating in a formerly incarcerated transition program in the southern United States. We identified several themes from our interviews. These themes were 1) PrEP information during incarceration; 2) Risky behaviors during incarceration and post-release; 3) Anticipated post-release challenges to accessing PrEP. Individuals formerly in prisons or other closed settings desire more education about PrEP during incarceration. They also want to learn more about HIV prevention measures. They believe that initiating PrEP in prison would allow a seamless transition to post-release PrEP programs. In conclusion, initiating PrEP during incarceration is one strategy to increase access to PrEP among the medically underserved criminal-justice population.